2019
DOI: 10.1016/j.heares.2018.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Sound-localization performance of patients with single-sided deafness is not improved when listening with a bone-conduction device

Abstract: An increased number of treatment options has become available for patients with single sided deafness (SSD), who are seeking hearing rehabilitation. For example, bone-conduction devices that employ contralateral routing of sound (CROS), by transmitting acoustic bone vibrations from the deaf side to the cochlea of the hearing ear, are widely used. However, in some countries, cochlear implantation is becoming the standard treatment. The present study investigated whether CROS intervention, by means of a CROS bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
44
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 36 publications
6
44
1
Order By: Relevance
“…For sound localization by BAHAs, Kim et al [10] reported that the percentage of correct sound localization was 13-65.8% before BAHA implantation and 15-68.5% after implantation, showing no significant difference in six studies. In a recent study, Agtrberg et al [12] reported that BAHA neither improved nor deteriorated the localization abilities of patients with SSD. Kitterick et al [11] reported that sound localization was not changed by CROS hearing aids in five studies and a significant deficit was indicated in one study.…”
Section: Baha and Cros Hearing Aidmentioning
confidence: 94%
See 1 more Smart Citation
“…For sound localization by BAHAs, Kim et al [10] reported that the percentage of correct sound localization was 13-65.8% before BAHA implantation and 15-68.5% after implantation, showing no significant difference in six studies. In a recent study, Agtrberg et al [12] reported that BAHA neither improved nor deteriorated the localization abilities of patients with SSD. Kitterick et al [11] reported that sound localization was not changed by CROS hearing aids in five studies and a significant deficit was indicated in one study.…”
Section: Baha and Cros Hearing Aidmentioning
confidence: 94%
“…For speech comprehension in noise, Blasco and Redleaf [12] conducted a metaanalysis and reported in the situation where both speech and noise were coming from the front; the signal-to-noise ratio for speech perception in noise was significantly improved following CI. However, in the situation where speech was coming from the front and noise was coming from the affected side, no improvement was observed.…”
Section: Cochlear Implantmentioning
confidence: 99%
“…Normal hearing listeners are highly accurate in their ability to localize sound in space, whereas this is largely disrupted in monaural listeners [35,36] due to the lack of available ITD and ILD cues. This hinders the ability of a monaural listener to accurately and rapidly orient themselves to signals of interest or importance.…”
Section: Unilateral Profound Deafnessmentioning
confidence: 99%
“…In 2001, the results of a series of 29 patients were reported indicating that SSD patients fitted with a BAHA could provide benefits in hearing in noise, in better hearing from the deaf side and in localisation . Several authors have confirmed hearing in noise benefits since that time but most of these studies did not demonstrate any improvement of sound localisation performance with BAHA and SSD . On the other hand, some older studies show that in case of total deafness in one ear, localisation blur decreases with experience and localisation becomes more natural even without any rehabilitation …”
Section: Introductionmentioning
confidence: 99%
“…7 Several authors have confirmed hearing in noise benefits since that time but most of these studies did not demonstrate any improvement of sound localisation performance with BAHA and SSD. 4,[8][9][10][11][12][13][14][15][16][17][18] On the other hand, some older studies show that in case of total deafness in one ear, localisation blur decreases with experience and localisation becomes more natural even without any rehabilitation. 19,20 Despite the lack of objective evidence that BAHA can improve localisation performance in patients with SSD, some of these patients have reported subjectively that their localisation ability was improved with the device.…”
mentioning
confidence: 99%